Correction: The effectiveness of problem based learning in improving critical thinking, problem-solving and self-directed learning in first-year medical students: A meta-analysis. - Ida Bagus Amertha Putra Manuaba; Yi -No; Chien-Chih Wu (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0277339.].